CARMENES: blue planets orbiting red dwarfs - Quirrenbach, Andreas; Amado, P. J.; Caballero, J. A.; Mandel, Holger; Mundt, Reinhard; Reiners, A.; Ribas, I.; Carrasco, M. A. Sánchez; Seifert, Walter; Azzaro, M.; Galadí, D. (Proceedings of the International Astronomical Union, 2013)
CARMENES (Calar Alto high-Resolution search for M dwarfs with Exo-earths with Near-infrared and optical Echelle Spectrographs) will conduct a radial-velocity survey of ~ 300 M dwarfs with the 3.5m telescope at the Calar Alto Observatory. The CARMENES instrument is currently under construction; it consists of two independent échelle spectrographs, which together cover the wavelength range 0.55 - 1.7μm at a spectral resolution of R = 82,000. The spectrographs and the fiber input are designed with a goal of 1m/s radial velocity precision using simultaneous calibration with emission-line lamps.
Published online by Cambridge University Press: 06 January 2014
Gesehen am 10.12.2021